Psychological and Psychosocial Interventions for PTSD, Depression and Anxiety Among Children and Adolescents in Low- and Middle-Income Countries: A Meta-Analysis - Uppendahl, Jana R.; Alozkan-Sever, Cansu; Cuijpers, Pim; de Vries, Ralph; Sijbrandij, Marit (Frontiers in Psychiatry, 2020)
Background In low- and middle-income countries, rates of common mental health disorders are found to be very high among children and adolescents while individuals, particularly in these countries, face barriers to mental health care. In the recent years, randomized controlled trials (RCTs) have been conducted that implemented and tested different psychological and psychosocial treatment approaches to treat common mental disorders. This review aims to analyze psychological interventions among children and adolescents in low- and middle-income countries. Methods RCTs carried out in low- and middle-income countries on psychological and psychosocial interventions for children and adolescents with symptoms of trauma- and stressor related disorders, depression or anxiety were identified in bibliographic databases. Databases were systematically searched until December 14, 2018. Effect sizes indicating differences between treatment and control groups at post-test were computed using a random-effects model. Outcomes were symptoms of depression, anxiety and posttraumatic stress disorder (PTSD). Results Thirteen studies with a total of 2,626 participants aged between 5 and 18 years were included. Treatments varied between studies and number of treatment sessions ranged from 1 to 16. The pooled effect size, combining outcomes of depression, anxiety and PTSD of psychological or psychosocial intervention versus care-as-usual or a control conditions yielded a medium effect (g=0.62; 95% CI: 0.27-0.98). Heterogeneity was very high (I2=94.41; 95% CI= 80-91). The beneficial effect of interventions increased after excluding outliers (g= 0.72; 95% CI: 0.37-1.07), while Heterogeneity remained high (I2=86.12; 95% CI=87-94). Conclusion High quality RCTs investigating the effect of psychological and psychosocial interventions on PTSD, depression and anxiety among children and adolescents in low- and middle-income countries are scarce. Results of the available studies may suggest that psychological and psychosocial interventions might be more effective in reducing symptoms of anxiety, depression and PTSD compared to control conditions. Due to very high heterogeneity, this evidence must be considered with caution.